Jurusan Keperawatan Poltekkes Kemenkes Bandung - Yulida S (Poltekkes Kemenkes Semarang, 2014)
In consideration of cost-effectiveness for the treatment of burn patients both as an effort to improve the quality of care, impact on the reduction of treatment time (Length Of Stay / LOS). So the shorter time will reduce maintenance costs, in Dr. Hasan Sadikin burn treatment using 0.9% NaCl and Moist Exposed Burn oitment or combination deengan sufratule, wearing modern treatments (woundress). Prontosan is a breakthrough as an alternative treatment of burns, the active substance content in prontosan also produce healing time relative faster or less 7-14 days compared with conventional therapy.This study is a comparative experimental study design that is observed on the observation that treatment and control, using a quasi-experimental design (quasi experiment designs),80% of respondents male sex, the wound healing process in a significant decrease prontosan the first day (12.5), day 5 (1.0), while on the first day of 0.9% NaCl (14) decrease occurred on day 8 (1.0), the difference between pre da post both the treatment group and the control group there was significant difference obtained p value less than 0.05.